Impact of Female Education on Fertility Status of Muslim Community of Susta Rural Municipality: Kudiya, Nawalparasi - Gyawali, Krishna Prasad (Saptagandaki Journal, 2021)
Background: This study explores the impact of female education on fertility status. Nepal has been experiencing a fertility decline over the last few decades. Although many factors have been shown to influence women’s childbearing, socioeconomic factors such as education and religion are some of the prime factors that mainly influence women’s fertility in Nepal. The major objective of this study is to examine the relationship between education and fertility behavior of the respondents. Methods: This study is descriptive in nature. Sample of this study consist the 218 married Muslim women randomly selected out of 689 families from Susta Rural Municipality of Parasi. Data were analyzed using the statistics like frequencies, percentages and mean value. Results: Level of education has inverse relation to fertility. The CEB between illiterate, literate, SLC and intermediate attainment women was found significantly different. Moreover, it was also found that most of the women had knowledge of family planning but they were reluctant to use family planning method. Conclusion: Major conclusion of this study indicated the inverse relationship between level of education and fertility behavior of Muslim women. Hence, fertility behavior can be changed through education policy intervention over Muslim women in rural area.